PENGARUH VARIETAS DAN JENIS PUPUK TERHADAP PERTUMBUHAN DAN HASIL CABAI RAWIT (Capsicum frutescens) - Abdurrohim; Sri Widata; Driska Arnanto (Universitas Sarjanawiyata Tamansiswa, 2026)
This research aims to determine the effect of varieties and types of fertilizer on the growth and yield of cayenne pepper. This research was conducted at the Self-Help Agricultural and Rural Training Center (PAS)